2020
DOI: 10.1155/2020/9076168
|View full text |Cite
|
Sign up to set email alerts
|

Complete Remission of Multiple Brain Metastases in a Patient with EGFR-Mutated Non-Small-Cell Lung Cancer Treated with First-Line Osimertinib without Radiotherapy

Abstract: Osimertinib has demonstrated efficacy against stable or asymptomatic central nervous system (CNS) metastases of epidermal growth factor receptor (EGFR) mutation-positive non-small-cell lung cancer (NSCLC) in phase 2 and 3 clinical trials that allowed prior CNS radiotherapy. However, the efficacy of osimertinib only or the optimal treatment combination or sequence of radiotherapy has not been investigated. A 74-year-old woman diagnosed with T4N1M1c Stage IVB lung adenocarcinoma with EGFR mutation presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Similar results supported that WBRT should be deferred or even withheld in another recent case report. Authors suggested that a multiple asymptomatic BM patient with EGFRm NSCLC treated with first-line osimertinib without RT reached iCR with the response of lung lesions (Ameku and Higa 2020 ). A case published in 2023 also reported an EGFRm NSCLC patient with symptomatic BM getting iCR after aumolertinib monotherapy (Shan et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results supported that WBRT should be deferred or even withheld in another recent case report. Authors suggested that a multiple asymptomatic BM patient with EGFRm NSCLC treated with first-line osimertinib without RT reached iCR with the response of lung lesions (Ameku and Higa 2020 ). A case published in 2023 also reported an EGFRm NSCLC patient with symptomatic BM getting iCR after aumolertinib monotherapy (Shan et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“… 41 When it comes to earlier generation TKIs, their concentration within the cerebrospinal fluid is less than that found in the blood which in turn results in treatment failure due to pharmacokinetic limitations. 42 Osimertinib, on the other hand, effectively penetrates the blood-brain barrier, resulting in higher brain exposure than the previously tested EGFR- TKIs. A positron emission tomography (PET) study with radio-isotope labeled osimertinib showed that the drug rapidly distributed within the brain, with a higher uptake into the grey compared to the white matter with a Tmax of 13 minutes (range 5–30min).…”
Section: Osimertinib In Patients With Central Nervous System (Cns) Metastasesmentioning
confidence: 99%
“…41 When it comes to earlier generation TKIs, their concentration within the cerebrospinal fluid is less than that found in the blood which in turn results in treatment failure due to pharmacokinetic limitations. 42 Osimertinib, on the other hand, effectively penetrates the blood-brain barrier, resulting in higher brain exposure than the previously tested EGFR-TKIs.…”
Section: Osimertinib In Patients With Central Nervous System (Cns) Metastasesmentioning
confidence: 99%
“… 15 Recent studies have indicated a role for next-generation EGFR-TKIs, such as osimertinib, in the treatment of CNS metastases. 16 Osimertinib is a third-generation EGFR-TKI approved in many countries around the world for first-line EGFRm advanced NSCLC and EGFR T790M mutation-positive advanced NSCLC, 17 , 18 and is now recommended as the preferred EGFR-TKI in guidelines, in part due to its proven CNS efficacy. In the recent ADAURA trial, adjuvant osimertinib reduced the risk of disease recurrence or death by 80% for stage IB-IIIA patients [hazard ratio (HR) 0.20; 99.12% confidence interval (CI) 0.14-0.30; P < 0.001] compared to a placebo.…”
Section: Introductionmentioning
confidence: 99%